DYNAMICS OF IMMUNE AND INFLAMMATORY MARKERS AFTER METABOLIC SURGERY: CLINICAL–MORPHOLOGICAL CORRELATIONS - Sultonov Erkin Yokubjon ugli (Bright Mind Publishing, 2026)
Metabolic surgery, commonly referred to as bariatric surgery, has evolved from a purely weight-reduction intervention into a powerful metabolic and immunomodulatory strategy. While its primary indication remains the treatment of severe obesity, accumulating evidence demonstrates that the benefits of metabolic surgery extend far beyond sustained weight loss. Profound changes in glucose metabolism, lipid homeostasis, hormonal signaling, and immune regulation have been documented following surgical intervention, positioning metabolic surgery as a key modifier of systemic inflammation and immune function.
Keywords: Metabolic surgery, commonly referred to as bariatric surgery, has evolved from a purely weight-reduction